Spectral analysis of layered sites using shaking table tests. - Gang Fan; Jianjing Zhang; Jinbiao Wu; Kongming Yan (PLoS ONE, 2019)
The dynamic response analysis of horizontal and inclined layered sites using large-scale shaking table tests in various directions, including the dip direction, strike, vertical direction, slope direction and direction perpendicular to the interface of layered sites is conducted in this study. The Fourier spectrum and response spectrum characteristics in the horizontal site are first investigated in this study, and the dynamic responses of the inclined layered sites are then studied and compared to the corresponding responses of the horizontal layered site. The influence of dip angle on the response spectrum is also studied.